Pentingnya Aktivitas Fisik bagi Remaja di SMA PGRI 2 Kota Jambi - Fadilla, Tanti Cintya; Azlita, Dara; Rezkiani, Salsa; Serigar, Melanie Putria Dewita; Khairunnisa, Yulia; Vifiyanti, Widya; Jannah, Raudhatul; Bizanti, Tiara Andia Ratu; Wulansari, Arnati (Jurnal Abdimas Kesehatan (JAK), 2024)
Low physical activity is one of the causes of obesity. Obesity occurs due to physical activity that is less than the body's needs due to the habits of teenagers who prefer activities inside the home rather than outside the home such as watching television and playing online games. The purpose of this community service activity is to provide education and understanding of what obesity is, the causes of obesity, the relationship between obesity and physical activity in SMA PGRI 2 Jambi City. Methods of implementation in the form of counseling, discussion, gymnastics, pre-post test and measurement of nutritional status. Monitoring evaluation is carried out by looking at indicators of success in the aspect of attendance, the target is to attend each meeting in community service activities, reflection and feedback from participants. The results of the activity show that school support is very good, the knowledge of students who have good knowledge is 64%. Collaboration with health workers is needed to gain new knowledge on a regular basis, as well as to empower students as youth cadres.